Qualitative screening of phytochemical constituent and preliminary toxicity of sansevieria cylindrical / Nur Hasanah Abu Hassan - Abu Hassan, Nur Hasanah (Faculty of Applied Sciences, 2014)
Sansevieria cylindrica is a species belong to Agavaceae family. Locally Sansevieria cylindrica is known as “Pokok Tanduk”. This species is an ornamental plant which is originated from Africa. Sansevieria cylindrica play a rule in medicinal field usually to treat inflammation. The aim of this work was to investigate the phytochemical constituent and its toxicity toward Artemia salina. The leaf of Sansevieria cylindrica was compared between outer rind and inner pulp which is extracted in aqueous and methanolic extract. The phytochemical screening showed the presence of tannins, saponins, flavonoids, anthocyanin, glycosides, steroid, phytosterols, terpenoids, cardiac glycoside and coumarine. All of these secondary metabolites extracted have its biological effect on human. Aqueous extract of Sansevieria cylindrica showed less toxicity compared to methanolic extract. The aqueous extract of outer rind showed least toxicity with LC50 207.84μg/ml. The methanolic extract of outer rind show the highest toxicity level with LC50 5.06μg/ml. Brine shrimp lethality bioassay and its biological active components indicates a potential character in pharmacological field.